Between Design and Culture: Research and Practices at PPGD/EBA/UFRJ - Peixoto, Irene de Mendoça; Araujo Pires, Julie; Mourthé, Claudia Rocha; Christo, Deborah Chagas; Cardoso , Fernanda de Abreu; Elias, Larissa; Oliveira, Madson; Paula , Marcus Vinícius de; Ponte, Raquel (DAT Journal, 2026)
This article presents the Design and Culture Research Line of the Graduate Program in Design at the School of Fine Arts of the Federal University of Rio de Janeiro (PPGD/EBA/UFRJ). Situated within the concentration area of Visual Design, this Research Line is grounded in the inseparable articulation between theory and practice, understanding design as a cultural practice and visuality as a social, historical, and political construction of the gaze. Through its Laboratories and Research Groups, the Line promotes interdisciplinary approaches in dialogue with visual culture, semiotics, critical theory, and artistic practices. To systematize its investigations, this article organizes the Research Line around three conceptual axes: Contemporary Visuality; Language, Meaning, and Communication; and Creative Processes, Poetics, and Material Becoming. It also emphasizes the convergence among research projects and related courses, particularly regarding critical and process-oriented approaches, as well as the education of researchers capable of problematizing contemporary visuality and intervening reflexively within the expanded field of visual design.